KEPEMIMPINAN PEREMPUAN DALAM JABATAN PUBLIK PERGURUAN TINGGI KEAGAMAAN - Ernardi Ernardi; Nirzalin Nirzalin; Fauzi Fauzi (Kalam: Jurnal Agama dan Sosial Humaniora, 2023)
The goal of this research is to determine the role and strategy of women's leadership in carrying out their responsibilities as leaders. The descriptive qualitative method was employed in this investigation. Women leaders at STAIN Teungku Dirundeng Meulaboh are thought to be competent of carrying out their obligations well, and they participate actively in organizational activities in every current field. Leaders can also supply subordinates with adequate job motivation, allowing them to accept their responsibilities. There are various essential factors that have a significant impact on his position as a public official, which may be evaluated in terms of societal values, social status, communication, education, and work experience. As a result, more effort must be done by the women leaders in question in order for them to be considered suitable for positions in each profession. Women's leadership in academic accomplishment is no different than men's leadership, but they prefer to favor emotions over enforcing discipline, making assertiveness difficult. Women's leadership strategies at STAIN Teungku Dirundeng Meulaboh include consulting and delegating strategies, planning and organizing strategies, problem solving strategies, clarifying strategies, monitoring strategies, motivation strategies, and recognition and appreciation strategies, as well as supporting strategies.